Sustainable logistics – a direction of counteracting development problems in cities on the example of Oświęcim - Paprzyca, Krystyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The technical infrastructure is one of the essential elements of the system associated with the idea of sustainable development. Urban transport is one of the components of technical infrastructure, and its quality and intensity are often a consequence of "urban sprawl". The phenomenon of uncontrolled spread of the city is currently encountered in many urban centres. It increases the length and time for travels and therefore transport costs. This phenomenon can also have many other negative consequences: – excessive use of land for communication purposes, <span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: 'Noto Sans',Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">– the increase of exhaust emission, <span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: 'Noto Sans',Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">– the increase in costs related to the use of the car, <span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: 'Noto Sans',Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">– the increase of noise on the streets, <span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: 'Noto Sans',Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">– increased number of road accidents, <span style="display: inline !important; float: none; background-color: #ffffff; color: #000000; cursor: text; font-family: 'Noto Sans',Arial,Helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">– social costs which include lack of exercise, sedentary lifestyle etc. There are various solutions proposed worldwide, the aim of which is to reduce the number of kilometres travelled by car. Such activities are possible due to all initiatives related to changing lifestyles that are introduced and supported by local government units in cities and municipalities. The goal of all actions aimed at efficient urban transport is to create an economically effective system that also reduces the nuisance to the environment. The problems related to the redesigning of existing streets are focused in particular on safety and limiting traffic. The efficient urban transport system is integrated with the issues related to the close neighbourhood and multi-model solutions connected with the choice of means of transport, as well as the high quality of public spaces and the quality of life of residents. The article discusses the above course of action on the example of the city of Oświęcim.